How Corporate Governance protects Indonesian Companies From Financial Distress - Novin Lesmana; Cacik Rut Damayanti (Universitas Diponegoro, 2021)
This research aimed to determine the influence of corporate governance which is proxied by the Independent Board of Commissioners, Board of Directors, Institutional ownership, and Financial Performance which is proxied by Return on Assets (ROA), Current Ratio (CR), Debt Ratio (DR) on Financial Distress as measured by Z-score. The importance of implementing corporate governance and corporate financial performance will help predict financial distress in company. This research is conducted in property, real estate and buiding construction sector listed in Indonesia Stock Exchange during the periods 2016-2018. The type of this reasearch is explanatory research, using a quantitative approach. This research was conducted on 17 samples of property, real estate and buiding construction companies listed in Indonesia Stock Exchange during the periods 2016-2018. Samples were obtained through purposive sampling method. The analysis technique is used multiple linier regression. The results show that Return on Assets, Current Ratio, Debt Ratio variables have a significant influence on financial distress. Variables Independent Board of Commissioners, Board of Directors, Institutional Ownership did not partially have a significant influence on financial distress.